Re-assembling knowledge production with(out) the university. (1st January 2019) - Muellerleile, Chris; Lewis, Nick
ABSTRACT: As an introduction to the themed issue, this paper interrogates the idea of university unbundling through a critical reading of Ronald Coase's theory of transaction costs. Coase, who was initially interested in the structure of firms, later applied his transaction cost theory more broadly to anything that might be defined as 'welfare'. Not unlike other abstract economic theories, in the age of market discipline, Coase's ideas have been widely employed to regulate the provision of public goods. Read through Coase, the main effect of the unbundling discourse has been to rationalise the university – to make it subject to a logic of efficiency as an end, and ultimately we suspect, to do damage to universities as important institutions for the cultivation of democratic values and socio-economic justice. After a brief summary of the other six papers included in the issue, the paper concludes with a discussion of the possibility of maintaining a public university in light of the neoliberal discourse of unbundling.